1979
DOI: 10.1002/star.19790310304
|View full text |Cite
|
Sign up to set email alerts
|

Factors Improving the Steeping Process of Corn Grains. Part I. Effect of Steeping Process, Artificial Drying, Scratching and Storage

Abstract: CairoIt was found that the steeping of corn grains by using the usual counter-current system is more efficient for leaching protein than the continuous system. Artificial drying of corn grains at higher temperaturedecreases starch recovery and increases starch loss in byproducts. The scratching of presteeped corn grains reduced the steeping period by 40%. Storage of corn grains for a long period (9 months) reduced starch recovery by about 3%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
3
1

Year Published

1980
1980
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
4
3
1
Order By: Relevance
“…One of the three hybrids (FR600× FR1087) showed lower starch yields at ambient conditions, one hybrid (1994, 1995, and 1996) showed no significant differences between storage conditions (4°C or ambient), and one hybrid (FR618×LH123HT) from the 1994 crop showed a lower starch yield at ambient conditions, but the same hybrid from the 1996 crop showed no significant difference between 4°C or ambient storage conditions. The lack of an effect of storage time on starch yield at a particular storage condition (4°C or ambient) is not in agreement with the results reported by Roushdi et al (1979) which showed a drop of 1.1, 1.9, and 2.5% in starch yield as storage time (at room temperature) increased from zero to three, six, and nine months, respectively. It is not possible to ascertain why this study does not agree with the Roushdi et al (1979) results.…”
Section: Resultscontrasting
confidence: 85%
See 3 more Smart Citations
“…One of the three hybrids (FR600× FR1087) showed lower starch yields at ambient conditions, one hybrid (1994, 1995, and 1996) showed no significant differences between storage conditions (4°C or ambient), and one hybrid (FR618×LH123HT) from the 1994 crop showed a lower starch yield at ambient conditions, but the same hybrid from the 1996 crop showed no significant difference between 4°C or ambient storage conditions. The lack of an effect of storage time on starch yield at a particular storage condition (4°C or ambient) is not in agreement with the results reported by Roushdi et al (1979) which showed a drop of 1.1, 1.9, and 2.5% in starch yield as storage time (at room temperature) increased from zero to three, six, and nine months, respectively. It is not possible to ascertain why this study does not agree with the Roushdi et al (1979) results.…”
Section: Resultscontrasting
confidence: 85%
“…The lack of an effect of storage time on starch yield at a particular storage condition (4°C or ambient) is not in agreement with the results reported by Roushdi et al (1979) which showed a drop of 1.1, 1.9, and 2.5% in starch yield as storage time (at room temperature) increased from zero to three, six, and nine months, respectively. It is not possible to ascertain why this study does not agree with the Roushdi et al (1979) results. Roushdi et al (1979) did not report or indicate any quality control of their wet-milling procedure.…”
Section: Resultscontrasting
confidence: 85%
See 2 more Smart Citations
“…Roushdi et al (1979) found that scratching presteeped corn grains facilitates penetration of the steeping water, reducing the steeping period by 40%. Wall and Paulis (1978) found that the treatment of corn with alkali disintegrates and disperses the matrix proteins, as well as facilitating the release of starch granules.…”
mentioning
confidence: 98%